BONEKA TANGAN SEBAGAI MEDIA PENINGKATAN KETERAMPILAN BERBAHASA PADA ANAK USIA DINI - Napitupulu, Dedi Sahputra; Suriaty, Suriaty (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2021)
Good language skills are very important skills in children. Even one indication of a child's intelligence at an early age level is measured by his fluency in language or speaking. This study aims to describe the use of hand puppet media to develop language skills in early childhood. This research uses descriptive qualitative method by using data collection techniques through interviews, observations and documents. Specifically, this study was conducted at Kindergarten ABA I Aek Kanopan. The results of this study show that hand puppets are very effectively used as a learning medium to develop early childhood language skills.